IMPROVING THE PARAGRAPH WRITING ABILITY THROUGH PROCESS STRATEGY AT SMA NEGERI 1 GOWA - Bahang, M. Dahlan (JOURNAL OF ADVANCED ENGLISH STUDIES, 2018)
The purpose of this study is to determine the extent to which processes and strategies can improve students' ability to write. In addition, this research is to determine students' ability to produce paragraphs. This type of research is classroom action research. The subjects consisted of 27 students who were class XI students of SMA 1 Gowa, a language program in the 2017/2018 academic year. The data of this study were collected using four types of instruments: observation sheets, field notes, portfolios, and the final composition of students in each cycle. The ability of students to write is analyzed using descriptive analysis and qualitative analysis. Descriptive analysis is used to analyze quantitative data consisting of percentages, averages, medians, modes, standard deviations, variants, frequencies, and tables. Qualitative analysis is used to analyze qualitative data which consists of the coding process of observations and field notes. The result shows that through process strategy, student’s writing ability can be improved, especially in writing paragraph.